Biochar production from sago (Metroxylon Spp.) via pyrolysis - Rambli, Jakaria (2019)
The limited of fossil fuels and the growing awareness of the detrimental environmental consequences resulting from greenhouse gas emissions have reinforced the importance of biomass as an energy resource in developed and developing countries. It is expected that future energy use will have increased utilization of different energy sources, including biomass, municipal solid wastes, industrial wastes, agricultural wastes and other low grade fuels. Recently, the ease of accessibility of sago biomass has drawn considerable interest of researches regarding the production of renewable energy. Pyrolysis is a good practical solution to solve the growing problem of landfills, with simultaneous energy extraction and nonleachable minimum residue. Pyrolysis also provides good solution to the problem of sago residue particularly in the region of Sarawak, Malaysia. Therefore, an effort is made in this study to utilize sago biomass as agricultural residue for the production of cost effective and environmental friendly fuel. Furthermore, the slow pyrolysis of sago biomass from different sources of the plant (bark, frond and cortex) by using Electrical Furnace Reactor was studied with the aim of producing solid pyrolysis product known as biochar, having promising properties and potential for use in traditional fossil coal applications. The study focuses on investigating of the role of best process parameters including reaction temperature, process time and nitrogen flow rate on production of biochar. The experiments were designed using central composite design (CCD) method and the optimization was performed by using response surface methodology. The characteristics of biochar based on its quality, distribution of chemical species, carbon conversion efficiency and thermal efficiency has been examined. Optimal conditions was obtained at the temperature of 400 ºC, 20 minutes of process time and nitrogen flow rate of 75 mL/min to result in the maximum yield of biochar at 47%. Moreover, the calorific value was remarkably improved from 22.16 MJ/kg to 25.92 MJ/kg as the biomass was turned into biochar. The locally sourced starch flours were utilized as binder to produce three different grades of briquettes from the produced biochar at different mixing ratios. The textural, morphological and thermal stability characteristics of the prepared briquettes were investigated by surface area analysis (Brunauer-Emmett-Teller equation), scanning electron microscopy (SEM), and Thermogravimetric analysis (TGA). The sago cortex was found to have lower ash content as compared to other types whereas the mean calorific value of the briquettes were found to be 21.63 MJ/kg, 23.23 MJ/kg and 22.33 MJ/kg for sago barks, sago fronds and sago cortex, respectively. Experimental results showed that sago biomass is a potential alternative fuel for current fuels.